Directing mouse embryonic neurosphere differentiation toward an enriched neuronal population. Issue Volume 37:Issue1(2014:Oct.) (9th July 2014) - Torrado, Ema F.; Gomes, Cátia; Santos, Gisela; Fernandes, Adelaide; Brites, Dora; Falcão, Ana S.
Abstract: Neural stem cells (NSC) are self‐renewing multipotent cells that have emerged as a powerful tool to repair the injured brain. These cells can be cultured as neurospheres, which are floating aggregates of neural stem/progenitor cells (NSPCs). Despite their high clonal expansion capacity, it has been suggested that in neurospheres, only a small percentage of cells are capable of proliferation and that this system is not efficient in terms of neurogenic competence. Thus, our aim was to develop a neurosphere culture method with a highly proliferative stem/progenitor cell population and particularly with a prominent neurogenic potential, surpassing some of the claimed weaknesses of the neurosphere assay. In our model, mouse neurospheres were harvested from neural tissue at E15 and after only 4 days in vitro (DIV), we have achieved highly proliferative primary neurospheres (81% Sox2 and 76% Ki67 positive cells) and a rather low number of cells expressing glial and neuronal markers (∼10%). After inducing differentiation, we have attained an enriched neuronal population (45% β‐III‐tubulin positive cells at 15 DIV). Using a simple methodology, we have developed a NSPC model that can provide a valuable source of neuronal precursors, thus offering a potential starting point for cell replacement therapies following CNS injury.